Statistical Characteristics Test of Nakagami Fading Channel Based on CvM Algorithm - WANG Tao, HE Yigang, NING Shuguang, SUN Hao, ZHU Zhanwei (Jisuanji gongcheng, 2022)
The Nakagami fading channel model can simulate different channel fading environments using different values of fading factor m, and the simulation data are in good agreement with the actual measured values, which are widely used in the field of channel simulation.However, at present, there are few studies on the credibility of the Nakagami fading channel model, and there is a lack of scientific comparison and verification methods.According to the channel statistical characteristic that the first-order envelope sequence of a typical Nakagami channel obeys the Nakagami distribution, a goodness-of-fit test method based on the Cramer-von Mises (CvM) algorithm is proposed.The ‘Gaussian+Rayleigh+ DC’ combination method is used to develop the Nakagami fading channel model, which obtains the channel output sequence, and extracts the envelope sequence.On this basis, the two-sample CvM test algorithm is used to test the goodness-of-fit between the theoretical distribution and the actual distribution of the envelope sequence, to evaluate the credibility of the Nakagami fading channel model.The results of the hardware-in-the-loop simulation show that, compared with the K-S test, chi-square test, and Z+chi-square fusion test algorithms, the CvM algorithm has better recognition performance for Nakagami fading channels under different m values and has advantages in reliability and complexity.Its recognition accuracies for Nakagami fading channels with a false alarm probability of less than 0.01 and a sample length of more than 300 000 reach 92.6% and 96.4%, whereas for the other channels tested, there is no false recognition.